The Association Between Sleep Duration and Weight Gain in Adults: A 6-Year Prospective Study from the Quebec Family Study - Chaput, Jean-Philippe (Associated Professional Sleep Societies, LLC, 2008)
STUDY OBJECTIVE: To investigate the relationship between sleep duration and subsequent body weight and fat gain. DESIGN: Six-year longitudinal study. SETTING: Community setting. PARTICIPANTS: Two hundred seventy-six adults aged 21 to 64 years from the Quebec Family Study. More than half of the sample is drawn from families with at least 1 parent and 1 offspring with a body mass index of 32 kg/m(2) or higher. MEASUREMENTS AND RESULTS: Body composition measurements and self-reported sleep duration were determined. Changes in adiposity indices were compared between short- (5–6 hours), average- (7–8 hours), and long- (9–10 hours) duration sleeper groups. After adjustment for age, sex, and baseline body mass index, short-duration sleepers gained 1.98 kg (95% confidence interval: 1.16–2.82) more and long-duration sleepers gained 1.58 kg (95% CI: 1.02–2.56) more than did average-duration sleepers over 6 years. Short- and long-duration sleepers were 35% and 25% more likely to experience a 5-kg weight gain, respectively, as compared with average-duration sleepers over 6 years. The risk of developing obesity was elevated for short- and long-duration sleepers as compared with average-duration sleepers, with 27% and 21% increases in risk, respectively. These associations remained significant after inclusion of important covariates and were not affected by adjustment for energy intake and physical activity participation. CONCLUSIONS: This study provides evidence that both short and long sleeping times predict an increased risk of future body weight and fat gain in adults. Hence, these results emphasize the need to add sleep duration to the panel of determinants that contribute to weight gain and obesity. CITATION: Chaput JP; Després JP; Bouchard C; Tremblay A. The association between sleep duration and weight gain in adults: a 6-year prospective study from the Quebec Family Study. SLEEP 2008;31(4):517-523.